Age at menarche and its association with preschool BMI among girls in Northern Norway - Henrik Lykke Joakimsen; Astrid Brendlien; Anne-Sofie Furberg; Christopher Sivert Nielsen; Guri Grimnes; Elin Kristin Evensen (PLoS ONE, 2025)
Background A decreasing age of menarche has been reported across the Western world. Early menarche is associated with unfavorable health outcomes. Aim The aims of this study were to describe the age at menarche in a general population sample in Norway and the associations between body mass index (BMI) categories at preschool (approximately 6 years of age) and age at menarche. Methods We used self-reported age at menarche among girls who participated in the population-based study Fit Futures 1 (FF 2010–2011), mostly born in 1994, to calculate age at menarche. The preschool BMI from health records was divided into BMI categories according to validated cutoffs on the basis of age and sex from the International Obesity Task Force (IOTF). We estimated the effect of preschool BMI on age at menarche via a linear regression model adjusted for socioeconomic status (SES). Results Among 500 girls with a mean age of 16.5 years (standard deviation (SD) ± 1.4), 497 (99%) had completed menarche. The mean age at menarche was 13.0 years (SD ± 1.2). According to the fitted linear regression model, preschool obesity was a statistically significant predictor of age at menarche and was associated with menarche 9.5 months earlier than a normal preschool BMI was. R2 estimated that preschool BMI could explain 3% of the variance in age at menarche. Conclusion The mean age at menarche in Northern Norway was 13.0 (SD ± 1.2) years, similar to previous Norwegian studies. Childhood obesity was associated with earlier age at menarche.